Make it someone’s job: Documenting the growth of the academic integrity profession through a collection of position postings - Vogt, Lisa; Eaton, Sarah Elaine (Canadian Perspectives on Academic Integrity, 2022)
We examine specific roles in higher education specializing in academic integrity. We collected publicly advertised job postings from 2018 to 2021 (N = 34) from Canada (n = 18), the United States (n = 14), and Australia (n = 2). Our review showed that academic integrity jobs can be situated within different units including student affairs, the library, or the teaching and learning centre among others. Salaries ranged from 49,000 CAD to over 100,000 CAD, with salaries in senior leadership positions generally not being listed in public postings. We conclude for academic integrity work to be recognized through dedicated positions and compensated in a manner that demonstrates the work is valued by the institution. We further call for increased professional learning and training opportunities for those whose work is specialized around academic integrity.